Experimental Investigations of Combustion: (95 WT.-%) HAN–Water Solution with High-SSA Activated Carbons. Issue 4 (3rd April 2019) - Atamanov, Meiram K.; Amrousse, Rachid; Hori, Keiichi; Mansurov, Zulkhair
ABSTRACT: The thermal decomposition of hydroxylamine nitrate (HAN) 95% water solution, a "green" alternative of fuel/oxidizer formulation to hydrazine nitrate, as a rocket propellant in the presence of the high-specific surface area (SSA)-activated carbons was investigated. It was shown that the linear burning rate increased for the system of HAN 95% water solution admixed with activated carbons compared to that of the 95% water solution HAN alone. Also, decomposition of the mixture (HAN spiked with rice husk (RH)-derived activated carbons by 1 mass %) was monitored by electron ionization–mass spectrometry (EI–MS) at different heating rates (from 16 to 128 K/min). EI MS analysis of the formation of major gas products (NO, NO2  and N2 O) at the HAN decomposition in presence carbon particles shown various results.